Challenging the Pathophysiologic Connection between Subdural Hematoma, Retinal Hemorrhage and Shaken Baby Syndrome - Gabaeff, Steven C. (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2011)
Child abuse experts use diagnostic findings of subdural hematoma and retinal hemorrhages as near-pathognomonic findings to diagnose shaken baby syndrome. This article reviews the origin of this link and casts serious doubt on the specificity of the pathophysiologic connection. The forces required to cause brain injury were derived from an experiment of high velocity impacts on monkeys, that generated forces far above those which might occur with a shaking mechanism. These forces, if present, would invariably cause neck trauma, which is conspicuously absent in most babies allegedly injured by shaking. Subdural hematoma may also be the result of common birth trauma, complicated by prenatal vitamin D deficiency, which also contributes to the appearance of long bone fractures commonly associated with child abuse. Retinal hemorrhage is a non-specific finding that occurs with many causes of increased intracranial pressure, including infection and hypoxic brain injury. The evidence challenging these connections should prompt emergency physicians and others who care for children to consider a broad differential diagnosis before settling on occult shaking as the de-facto cause. While childhood non-accidental trauma is certainly a serious problem, the wide exposure of this information may have the potential to exonerate some innocent care-givers who have been convicted, or may be accused, of child abuse.